Effects of the Addition of Nb and V on the Microstructural Evolution and Hydrogen Embrittlement Resistance of High Strength Martensitic Steels. (24th February 2022) - Liu, Bo; Liao, Xiaolin; Tang, Yuanshou; Si, Yu; Feng, Yi; Cao, Pengjun; Dai, Qingwei; Li, Kejian
Abstract : Hydrogen embrittlement can easily occur in high strength martensitic steel, manifesting itself as a sudden failure or fracture without warning and greatly threatening the safety of automotive applications. Optimizing the composition of the alloy can be performed by matching heat treatment processing methods and controlling the precipitation amounts to form hydrogen traps. In doing so, the hydrogen embrittlement susceptibility of steel can be effectively delayed, reducing the risk of hydrogen-induced delayed cracking. In this study, four kinds of 1500 MPa strength grade martensitic steel were selected for testing and supplemented with different loadings of Nb and V, respectively. Their grains, phases, and precipitations were compared by optical microscopy (OM), electron backscattered diffraction (ESBD), and transmission electron microscopy (TEM) analyses. After the addition of Nb and V, the microstructure was refined, the residual austenite content increased, and the hydrogen embrittlement resistance was significantly improved.